Development of a Solar-Powered IoT-Based Flood Monitoring and Early Warning System with LoRa32 and TTN Integration for Remote Area Applications - MIMI NORMAZLEEN MOHAMAD SOM; MOHD HEZRI MOHD LWI@MOKHTAR (Progress in Engineering Application and Technology, 2026)
The recent increase in flooding across Malaysia is partly because of climate change and faster urbanization, mostly where drainage systems are not well developed. Poorly maintained and old flood sensors like in Klang Valley in 2021 meant warnings were slow to reach people and many were cut off from rescue help. Because of a weak monitoring system and limited communication, rural areas are more vulnerable and many have stopped listening to real alarms after multiple false ones. For this reason, this project establishes a solar-powered sensor network system for flood monitoring and early warning in rural communities using LoRa32 and The Things Network (TTN). It gathers environmental data with an ultrasonic water level sensor and a rain sensor which sends information via LoRaWAN and is checked in real time on a monitor. As soon as system levels reach critical amounts, Telegram notifications are sent out. Even without a power source, this system will not stop since it is charged by a solar panel and battery. Using green energy and wireless communication allows this solution to address the problems of disconnected rural communities facing floods. The purpose of this project is to make it easier for people to face floods by providing a more reliable and faster warning system.